Students’ Avoidance of English Use in English MKU During and Post-Pandemic - Caromawati, Corry; Dwinaya, Levita (Journal of Foreign Language Teaching and Learning, 2000)
Background: English as a general subject, known as Mata Kuliah Umum (MKU) in Indonesian tertiary education, primarily aims to develop students’ second language (L2) proficiency. These courses are therefore designed to encourage the use English during classroom interactions. However, many students choose to remain silent or resort to using Indonesian instead. Objective: This study examines students’ unwillingness to communicate/participate in English during classroom instruction, both during and post pandemic. Methods: It employs the third generation of the Activity Theory as the analytical framework, with the units of analysis being activities across the micro, meso, and macro levels. Using a case study approach, data were collected from multiple perspectives–students, teachers, and policymakers– through interviews. Course syllabi were analyzed as part of the dataset. Findings: The findings suggest that the policy makers’ decisions influenced the communication behaviour in both online and offline classes. This study highlights the importance of fostering L2 use habits through policymaking strategies such as aligning instructional practices with intended learning outcomes, establishing explicit language-use rules, and providing supportive tools and learning environments. Conclusion: Additionally, it emphasizes the need for teachers to deepen their understanding of the Communicative Language Teaching Approach (CLTA), particularly in balancing the development of both fluency and accuracy.